Scoring with Code: Composing with algorithmic notation. Issue 3 (13th November 2014) - Magnusson, Thor
<x content-type="archive" xml:space="preserve">Abstract</x> Computer code is a form of notational language. It prescribes actions to be carried out by the computer, often by systems called interpreters. When code is used to write music, we are therefore operating with programming language as a relatively new form of musical notation. Music is a time-based art form and the traditional musical score is a linear chronograph with instructions for an interpreter. Here code and traditional notation are somewhat at odds, since code is written as text, without any representational timeline. This can pose problems, for example for a composer who is working on a section in the middle of a long piece, but has to repeatedly run the code from the beginning or make temporary arrangements to solve this difficulty in the compositional process. In short: code does not come with a timeline but is rather the material used for building timelines. This article explores the context of creating linear 'code scores' in the area of musical notation. It presents the Threnoscope as an example of a system that implements both representational notation and a prescriptive code score.